From quarks and gluons to hadrons: chiral symmetry breaking in dynamical QCD - Braun, Jens; Fister, Leonard; Pawlowski, Jan M.; Rennecke, Fabian (Physical review, 2016)
We present an analysis of the dynamics of two-flavor QCD in the vacuum. Special attention is paid to the transition from the high-energy quark-gluon regime to the low-energy regime governed by hadron dynamics. This is done within a functional renormalization group approach to QCD amended by dynamical hadronization techniques. These techniques allow us to describe conveniently the transition from the perturbative high-energy regime to the nonperturbative low-energy limit without suffering from a fine-tuning of model parameters. In the present work, we apply these techniques to two-flavor QCD with physical quark masses and show how the dynamics of the dominant low-energy degrees of freedom emerge from the underlying quark-gluon dynamics.